B. If you multiply 1/12 by (-x) it's -1/12x and if you multiply 1/12 by (-4) it's -4/12 which is equivalent to -1/3.
Answer:
(1,4)
Step-by-step explanation:
Answer:
Cost of a pound of chocolate chips: $3.5
Cost of a pound of walnuts: $1.25
Step-by-step explanation:
x - cost of a pound of chocolate chips
y - cost of a pound of walnuts
We create two equations based on the information we have:
3x+2y=13
8x+4y=33
The whole point of these problems os to get rid of x or y. In this question, we can do this by multiplying both sides of the first equation by 2, and then subtracting it from the second equation:
8x+4y=33
6x+4y=26
2x=7
x=3.5
Then we change x for 3.5 in the first equation:
3×3.5+2y=13
10.5+2y=13
2y=2.5
y=1.25
Hope this helps!
No there totally differnt
Unless unusually unusual unification under